LIVING ON THE FRONTLINE OF ENVIRONMENTAL ASSAULT: LESSONS FROM THE UNITED STATES MOST VULERABLE COMMUNITIES - Bullard, Robert D.; Johnson, Glenn S.; Smith, Sheri L.; King, Denae W. (Revista de Educação, Ciências e Matemática, 2014)
<span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: Garamond; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; layout-grid-mode: line;" lang="EN-US">This paper presents the historical foundations and social context of the environmental justice movement in the United States. It provides a critique of government policies and industry practices that endanger the health and safety of African Americans and other minority groups. It examines the role of grassroots groups, community based organizations, and black institutions in dismantling the legacy of environmental racism, exploring some emblematic cases such as the post-Katrina and the BP oil spill in 2010. The paper reveals that environmental injustice remains a major barrier that impede millions of people of color from achieving healthy, livable, and sustainable communities.